2002
DOI: 10.1111/1532-7795.00032
|View full text |Cite
|
Sign up to set email alerts
|

He Said, She Said: Gender Differences in Mother – Adolescent Conversations about Sexuality

Abstract: This study examined gender differences in self-reported and observed conversations about sexual issues. Fifty mother-adolescent dyads reported on their conversations about sexual issues and participated in videotaped conversations about dating and sexuality in a laboratory setting. Gender differences (more mother-daughter than mother-son) were found in the extent of sexual communication based on adolescents' reports, but no gender differences were found based on mothers' reports, or on observations of conversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 28 publications
1
36
2
2
Order By: Relevance
“…In fact, in our own observational work, when asked to talk about "dating and sexuality," mothers and adolescents spent about 40 percent of conversations talking about dating, 17 percent talking about sex, and 38 percent off topic (Lefkowitz et al, 2002). However, topics coded "off topic" may have also been tangentially relevant to sex-related communication.…”
Section: Content Of Sex-related Communicationmentioning
confidence: 86%
See 3 more Smart Citations
“…In fact, in our own observational work, when asked to talk about "dating and sexuality," mothers and adolescents spent about 40 percent of conversations talking about dating, 17 percent talking about sex, and 38 percent off topic (Lefkowitz et al, 2002). However, topics coded "off topic" may have also been tangentially relevant to sex-related communication.…”
Section: Content Of Sex-related Communicationmentioning
confidence: 86%
“…For example, mothers and offspring sometimes engaged in metacommunication about sex, for instance, talking about whether a daughter had learned about sex in health class. Other mother-offspring pairs ended up off topic through the natural flow of conversation, for example, by first discussing when the child might be old enough to start dating, but then naturally moving to a discussion of growing up more generally (Lefkowitz et al, 2002).…”
Section: Content Of Sex-related Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…This apparent gender difference is not entirely without precedent, as previous findings have suggested that parents" conversations about sex with their daughters are more predictive of subsequent behavior than are parents" conversations with their sons (McNeely, Shew, Beurhing, Sieving, Miller, & Blum, 2002), potentially due to the more interactive nature of the conversations between mothers and daughters (Lefkowitz, Boone, Sigman, & Au, 2002). Primary analyses suggesting that the negative association between maternal control and subsequent risky sexual behaviors is suppressed by declining mother-adolescent engagement for boys provide some evidence to support this idea.…”
Section: Maternal Control and Adolescent Problemmentioning
confidence: 88%